Community Empowerment Strategy for the Development of Aren Sugar Production Center in Koto Malintang, Lake Maninjau, West Sumatra - Aswaldi Anwar; Ami Sukma Utami; Muhammad Parikesit Wisnubroto; Adrinal Adrinal; Ujang Khairul; Rafdi Pratama; Muhammad Adib; Rival Prasetyo; Rahma Susila; Novi Rahmat Itra (Departemen Budidaya Tanaman Perkebunan, Fakultas Pertanian, Universitas Andalas, 2025)
This community service program was implemented in Koto Malintang, West Sumatra, to empower farmer groups through the development of an Aren sugar (Arenga pinnata) production center. The activities consisted of pre-surveys, focus group discussions (FGDs), socialization workshops, participatory planning, and initial demonstrations of intercropping practices. A key component of the program was the financial feasibility analysis, designed to provide farmers and stakeholders with evidence-based tools for decision-making. The analysis was conducted using production costs and revenues from the research location, with a 15-year horizon and a 10% discount rate. Two cultivation scenarios were evaluated: (1) Aren intercropped with seasonal crops and (2) Aren intercropped with robusta coffee. Each scenario considered two product alternatives: molded sugar (gula cetak) and palm sugar crystals (gula semut). The results revealed that molded sugar offered only marginal feasibility, with Net Present Values (NPV) of Rp 28–35 million/ha, Internal Rates of Return (IRR) of 12–15%, Benefit-Cost (B/C) ratios around 1.1, and payback periods of 7–8 years. In contrast, palm sugar crystals showed strong financial viability, with NPVs of Rp 298–330 million/ha, IRRs of 38–45%, B/C ratios of 2.4–2.6, and payback periods of only 4–5 years. Sensitivity analysis confirmed robustness across discount rates of 8–12% and price variations between Rp 40,000–60,000/kg. These findings suggest that palm sugar crystals should be prioritized as the flagship product for Koto Malintang’s Aren sugar industry, supported by institutional strengthening, diversification, and modern marketing to ensure sustainability.